2016
DOI: 10.22159/ajpcr.2016.v9s3.12959
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thyroid Function Test in Obese Patients

Abstract: Objective: To evaluate thyroid function in 20-50 aged obese people. As obesity is a widespread problem today, knowledge about the factors affectingor influencing it is important. Little is known about the changes in thyroid function obese people. Influence on thyroid hormone synthesis has beenproposed.Methods: Thyroid function test was done for 30 obese and 30 nonobese people, and their thyroid-stimulating hormone (TSH) levels were compared.Results: Using paired t-test, we found that there is a statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…As BMI increases, the level in TSH hormone increases leading to hypothyroidism as similar to study conducted by Fathima et al in 2016. 14 In our study as BMI is over 35, no cases had normal TSH values. However, we have also found that normal thyroid function was found in 54 cases with obese which was quite similar to study by Strata et al,.…”
Section: Discussionmentioning
confidence: 53%
“…As BMI increases, the level in TSH hormone increases leading to hypothyroidism as similar to study conducted by Fathima et al in 2016. 14 In our study as BMI is over 35, no cases had normal TSH values. However, we have also found that normal thyroid function was found in 54 cases with obese which was quite similar to study by Strata et al,.…”
Section: Discussionmentioning
confidence: 53%
“…The circadian rhythm also plays an in luential role in the sleep-wake cycle (Rj and Devi, 2016;Fathima and P, 2016;Harsha et al, 2015). There was research done on the topic of pathogenesis and novel drugs, and the result conveyed that this pathogenesis and novel drug can be used for the testament and the assessment of asthma (Dave and Preetha, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Thus it states that obesity and altered cortisol levels contribute to the impact of type 2 diabetes mellitus, which results in the decreased verbal declarative memory performance. (Fathima and P, 2016). The physical itness relaxes our mind, which helps in improving mem-ory (David et al, 2019).…”
Section: Figure 6: Bar Chart Depicting the Association Between Gendermentioning
confidence: 99%